THE ASSESSMENT OF THE RICE FIELD SUSTAINABILITY IN JAVA BASE ON REGIONAL SPATIAL USE PLANNING (RSUP) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Abstract The sustainability of the rice field in Java as the main rice producer land in Indonesia is induced by the rice field conversion into settlement and indusfrial areas due to increase of population. These conversions cause decreasing of both quantity and quality of the land As mentioned in the Government Act Number 26/2007 concerning the Spatial Use Planning (SUP), the goal of SUP is to protect spatial use function of the land and to prevent negative impacts to the environment as a result of unproper land management The objective of this study is to assess the consistency of governmental policies in implementing the Act Number 26/2007 to achieve the rice field sustainability on the basis of agro-ecological concept By using the GIS modelbase, the rice field agro-ecological zones which are proposed as the standard rice field areas for the benchmark of the sustainable rice field agriculturemanagement system are synthesized from the spatial database of land system, land cover, agro-climate, irrigationcondition, social and economic data from the administration boundary layers. The results of this study show that the governmental policies from non-agricultU/:a1 sector in allocating the area status of the settlement areas as presented at the provincial regional spatial planning map (RTRW map) have not been fully consistent with the regulations as stated in Act Number 26/2007 for protecting a productive rice field function as the national rice producer. The potential loss of the rice production which is caused by the implementation of the rice field conversion into settlement areas and is allocated to the productive rice field agro-ecologicalzones is predicted 3.5 milliontons per year. Keywords: rice field agro-ecological zone, spatial use management, GIS modelbase, land conversion